Safe Assets' Scarcity, Liquidity and Spreads - Gabriella Chiesa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper constructs a simple general equilibrium model to analyse the interactions between the financial and the real sector in an environment where liquidity holdings is an input of the credit/investment process. The supply of liquidity is constrained in that income pledgeability limits inside liquidity, and not all sovereign debt is safe/liquid. We pin down the determinants of liquidity/collateral premia and bond spreads, and with reference to the eurozone: (i) the implications of the ECB's policies on liquidity provision and credit, and (ii) the debt management policy that would increase welfare with no need for transfer payments.
Keywords: E44; H63; G18; 330